The Ratio Legis of Government Regulation in Lieu of Law as Emergency Legislation - Putra Perdana Ahmad Saifulloh; Firdaus Arifin; Novendri M Nggilu; Dindha Shahrazade Sulaiman; Musa Sarjo (CV. Pustaka Parawali, 2026)
This study aims to examine the hierarchy, the meaning of urgent necessity, and the substance of Government Regulations in Lieu of Law (Perppu) from the perspective of emergency constitutional law. This study contributes to efforts to emphasise the importance of regulatory reform regarding the formulation of legislation, which is necessary to: First, clarify the hierarchy of Perppu within the legal system, as it is inappropriate to equate Perppu-as emergency legislation-with Law, which is legislation under normal conditions. Therefore, Perppu need not be included in the legislative hierarchy. Secondly, to clarify the meaning of urgent necessity as a prerequisite for the President to issue a Perppu. Thirdly, to clarify the substantive content of Perppu. This research is a normative legal study employing a juridical, historical, and conceptual approach. The findings indicate that the current regulation of Perppu does not fully reflect the concept of emergency legislation, particularly regarding hierarchy and substantive content. Legal reform is required to strengthen the position of the Perppu as an emergency legislation within Indonesia’s constitutional system, so that its use can be strictly and clearly limited and issued only when the state is in a state of emergency. The recommendations of this study are to reconstruct the hierarchy, clarify the meaning of ‘urgent need’, and define the content of the Perppu so that it meets the requirements of emergency legislation.